INTEGRASI POLA OPERASI BENDUNGAN DAN BENDUNG BERBEDA BASIS WAKTU UNTUK KEBUTUHAN IRIGASI - , RIDWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Weir and dam were artificial water resources made for specific purpose which played important role in flood management and concervation, including clean water supply, recreation, navigation, irrigation, and electric power plant. Management of dam and its reservoir should be based on operation and maintenance manual. Operation failure can possibly becaused by climate change or the increase discharge release demand during particular operation cycle. This study aimed to analyze operation system integration between dam and weir with different time base to meet water irrigation demand based on reliability and resiliency. Research was conducted in six sustainable analysis stages: (1) supply analysis on rain-stream distribution in watershed area between weir and dam